The Washington Consensus: some Implications for Latin America (2017)
Many countries in Latin America undertook sweeping economic reforms in response to the debt crisis, which were fostered by multilateral agencies such as the IMF and were aligned with the guidelines offered by the Washington Consensus. However, and after more than 25 years of application, many results achieved under the said consensus in economic and social matters are contradictory; therefore, this document reviews some shortcomings of its design and considers certain recommendations of adjustment, particularly in taxation. The paper states that the lack of internal consistency of the model and the weakness of certain assumptions on which it was based, such as the alleged inefficiency of State, limited the fulfillment of its objectives.